'She was there if I needed to talk or to try and get my point across': specialist advocacy for parents with intellectual disability in the Australian child protection system. Issue 2 (4th May 2018) - Collings, Susan; Spencer, Margaret; Dew, Angela; Dowse, Leanne
ABSTRACT: Parents with intellectual disability are overrepresented in child protection matters due to a combination of socioeconomic disadvantage and assumptions of parenting incapacity by child welfare workers and courts. Inability to understand the investigation process or instruct a solicitor can deny these parents equal access to justice. Specialist support can ensure parents exercise their legal capacity to participate in proceedings and have their views heard. Semi-structured interviews were undertaken with parents with intellectual disability ( n = 10) who accessed a specialist advocacy programme in New South Wales, Australia. Thematic analysis was used to identify the influence of advocacy on parents' experiences. Parents felt powerlessness as they navigated a bewildering child protection and court system that had prejudged them unfit to parent. This compounded the grief and loss of child removal. The advocate played a critical role in creating a bridge between parents and professionals. This helped to build parents' skills and confidence and improve the disability awareness of professionals. Specialist advocacy for all parents with intellectual disability in care proceedings is consistent with Australia's obligations under the Convention on the Rights of Persons with Disabilities.